Enhancement of anammox performance in a novel non-woven fabric membrane bioreactor (nMBR) - Ren, Long-Fei; Liang, Shuang; Ngo, Huu Hao; Guo, Wenshan; Ni, Shou-Qing; Liu, Cui; Zhao, Yuan-Kun; Hira, Daisuke (RSC Advances, 2015)
To reduce operating costs and membrane fouling of conventional membrane bioreactors (cMBR), a novel MBR using a non-woven fabric membrane (nMBR) was constructed and the performance of the two MBRs was compared for anaerobic ammonium oxidation (anammox) cultivation. The results showed that the start-up period for the nMBR (44 days) was notably shorter than that for the cMBR (56 days), meanwhile the nMBR achieved a 2-times higher nitrogen removal rate (231.5 mg N per L per d) compared to the cMBR (112.3 mg N per L per d). Illumina MiSeq sequencing showed that Candidatus Kuenenia and Candidatus Jettenia were the main distinguished anammox bacteria. FISH analysis revealed that anammox bacteria predominated in both reactors, especially in the nMBR (58%) corresponding to a qPCR analysis of 1.07 × 10 9 copies per mL (day 120). N 2 O emission analysis confirmed the advantage of the nMBR in N 2 O reduction to reduce the influence of greenhouse gas emission while treating identical nitrogen. These results clearly demonstrated that nMBRs could be a prospective choice for anammox start-up and performance enhancement.